Cathédrale des ondes ou éléphant blanc ? - Volker Ziegler (In Situ)
The Europe 1 transmitter center in Berus-Überherrn is a site of memory that carries the history of Saarland, a region that is semi-autonomous since the end of World War II and where Franco-German relations are deeply engrained. Installed in 1954-55, only a few meters away from the French border so as to bypass the public broadcasting laws in France, which did not allow private radio and television stations, it was part of the so-called “peripheral” radios whose main market was France. To ensure their market share, these private radios had to equip their stations with the most advanced transmission technologies. The eventful history of the construction of the transmission structure, with its huge roof made of a thin concrete veil, is associated with Bernard Laffaille, René Sarger and Eugène Freyssinet, three famous French engineers, with the later addition of Pierre Xercavins who consolidated the construction in the early 1980s. The symbiosis between the modern transmission technique and avant-garde construction, make this “cathedral of waves” a key work in post-war Europe and a unique landmark on the border’s landscape. The transmitter is one of the significant historical monuments of the 20th century in Saarland since as early as 1999, but it is unused since 2015. The sustainable preservation of this exceptional building, which will be designated as a "landmark of engineering in Germany" in 2021, is being heralded as a political objective on all levels.